ARTIFICIAL INTELLIGENCE DRIVEN INFRASTRUCTURE SECURITY ENHANCING CYBERSECURITY AND PROTECTING NATIONAL SECURITY SYSTEMS - Chowdhury Amin Abdullah; Md Jahidul Islam Ridoy (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: Artificial Intelligence (AI) functions as a fundamental technological solution which defends national security systems through improved cybersecurity infrastructure against sophisticated cyber threats. The fast growth of digital technology has made vital infrastructure systems vulnerable to cyber threats which include phishing attacks and ransomware and malware infections and data breach incidents. Method: The research used a quantitative survey-based design which collected data from 175 participants worked as cybersecurity professionals and IT experts and government officials and academic researchers. Descriptive statistics to analyze data through frequency and percentage and mean and standard deviation and ranking analysis and Pearson correlation which studied the connection between AI adoption and cybersecurity performance indicators. Results: The study found that 81.1% of participants selected phishing attacks as their primary security risk while ransomware attacks received 77.7% and data breaches obtained 73.7% of the votes. Correlation data revealed that countries which adopt AI technology tend to experience better national security results with r = 0.77 and improved threat detection with r = 0.74 and stronger data protection with r = 0.69. The system provides multiple benefits to users but users encounter three major obstacles which include privacy concerns at 74.3% and insufficient qualified staff at 71.4% and costly setup expenses at 69.1%. Novelty: AI functions as a fundamental element which enhances both cybersecurity systems and protects national security interests.